2010
DOI: 10.1021/bi1013003
|View full text |Cite
|
Sign up to set email alerts
|

Seipin Is a Discrete Homooligomer

Abstract: Seipin is a transmembrane protein that resides in the endoplasmic reticulum and concentrates at junctions between the ER and cytosolic lipid droplets. Mutations in the human seipin gene, including the missense mutation A212P, lead to congenital generalized lipodystrophy (CGL), characterized by the lack of normal adipose tissue and accumulation of fat in liver and muscles. In both yeast and CGL patient fibroblasts, seipin is required for normal lipid droplet morphology; in its absence droplets appear to bud abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 40 publications
7
89
1
Order By: Relevance
“…We have previously shown that within cells the lipins form tetramers (34), and by atomic force microscopy, we have found that recombinant lipin 1 can form even higher order structures on lipin bilayers (35). In addition, lipin 1 has been found to interact with the human lipodystrophy protein seipin (36), and seipin itself has been found to form large oligomeric structures (37)(38)(39). Although the identification of lipin localization to punctate spots is interesting, further study will be necessary to uncover the nature and/or function of lipin protein cellular localization to these structures.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that within cells the lipins form tetramers (34), and by atomic force microscopy, we have found that recombinant lipin 1 can form even higher order structures on lipin bilayers (35). In addition, lipin 1 has been found to interact with the human lipodystrophy protein seipin (36), and seipin itself has been found to form large oligomeric structures (37)(38)(39). Although the identification of lipin localization to punctate spots is interesting, further study will be necessary to uncover the nature and/or function of lipin protein cellular localization to these structures.…”
Section: Discussionmentioning
confidence: 96%
“…A potential candidate protein involved in mediating such an interaction in yeast is Fld1, the yeast orthologue of mammalian seipin, mutations of which are implicated in a severe inherited SeipBerardinelli congenital lipodystrophy (Fei et al, 2008b;Szymanski et al, 2007). Yeast seipin is an oligomeric transmembrane protein that localizes to the interface between lipid droplets and the ER, and was suggested to play a role in organizing lipid droplets (Binns et al, 2010). Yeast mutants lacking Fld1 show a diverse pattern of lipid droplets in the cell population, differing in both size and subcellular distribution (Fei et al, 2008b;Szymanski et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A prime candidate protein involved in mediating contacts between lipid droplets and the ER membrane is Fld1, the yeast seipin, because its absence results in an abnormal lipid droplet morphology that is also dependent on the cultivation conditions (Binns et al, 2010;Fei et al, 2008b;Szymanski et al, 2007). In our experiments, cells were cultivated either in rich medium or in SC minimal medium to stationary phase, at which time point, differences in the distribution of lipid droplets in wild-type and fld1D mutant cells are more pronounced.…”
Section: Dynamics Of Lipid Droplets Is Impaired In a Seipin-deficientmentioning
confidence: 99%
See 1 more Smart Citation
“…While physiological binding partners of seipin have yet to be identifi ed, it is clear that seipin can self-associate ( 51,59 ). When extracted from yeast membranes with Triton X-100, seipin behaves as a discrete and stable oligomer.…”
Section: Domains Topology and Oligomerizationmentioning
confidence: 99%